Subungual tumor of the hallux: a diagnostic challeng - Talissa Oliveira Generoso; José Felipe Marion Alloza; Renée Zon Filippi; Reynaldo Jesus-Garcia Filho (Journal of the Foot & Ankle, 2022)
Subungual tumors of the hallux are rare, with a varied spectrum of differential diagnoses, and it may be challenging to reach the correct diagnosis. Depending on the health system where the patient will be treated, the specialist physician may follow different paths in the search for pathological definitions, which may lead to delays in obtaining the diagnosis and even to mistaken results. We present a case of a patient with a subungual tumor of the hallux, which represents the singular process above, aiming to demonstrate relevant differential diagnoses, determining factors for the correct diagnosis, and the importance of pathological elucidation for its proper treatment so that the outcomes for the patient are prevented. Level of Evidence V; Case Report; Expert Opinion.